Evaluation of the longitudinal deformation of left ventricle and its changes in myocardial infarction and coronary heart disease with obstructive coronary artery lesions - N.V. Tytarenko; M.P. Kopytsya; I.V. Rodionova; A.V. Kobets (Кардіохірургія та інтервенційна кардіологія)
The review provides data on a new method of ultrasound diagnostics – speckle tracking echocardiography in the diagnosis of myocardial infarction and coronary heart disease with obstructive coronary artery lesions, the advantages of the global longitudinal strain (GLS) compared to the existing echocardiographic indicators of global systolic and segmental systolic function. The value of measuring GLS in coronary heart disease is the quantitative detection of wall motion abnormalities, when left ventricular ejection fraction is within normal values and visual assessment does not detect violations of regional contractility. In patients with myocardial infarction without ST-segment elevation, GLS measurement may assist in the selection of patients who need urgent reperfusion therapy. In coronary heart disease, GLS can complement the conventional assessment of wall movement; replace the need for additional non-invasive testing for some patients with suboptimal stress tests. The normal limits of the GLS for various manufacturers of ultrasound scanners and technical characteristics for the correct studying of the GLS are described. The value of the GLS gradually decreases in mild, moderate and severe forms of coronary heart disease, and is the lowest in patients with myocardial infarction with ST segment elevation. The possibilities of detecting infarct-related coronary artery using the amplitude of the segmental strain and the «bull’s eye» diagram in isolated lesions of one of the coronary arteries are described. The analysis of the strain curves is carried out, the characteristics of the strain curve in normal conditions and in ischemia are presented. The probable signs of ischemia are the phenomena of early systolic lengthening and postsystolic shortening on the curves of longitudinal deformation. The conditions when the postsystolic contraction on the strain curve is pathological are described.